Education, equality and human rights issues of gender, 'race', sexuality, disability and social class - Cole, Mike 1946- (Routledge, Taylor & Francis Group, 2023)
"This book offers an uncompromising and rigorous analysis of education and human rights by examining issues related to gender, race, sexuality, disability and social class. Written as a companion to the very successful U.K. version, this volume reflects the economic, political, social and cultural changes in educational and political policy and practice in the United States. Offering a comprehensive look at these areas, this book is an essential resource across a wide range of disciplines and for all those interested in education, social policy and equality"--